Political Ethics As A Human Political Dimension In Creating A Democratic Law State - Farah Diba Maria Ulfa; Ratna Herawati (ARISTO, 2022)
Political ethics is needed in all conditions of a country, whether they are normal, chaotic, or under control. To discuss authority in chaotic circumstances, it needs political ethics, in which every political action requires legitimacy based on values, norms, and laws. The discussion on political ethics is related to law and state power. The role of law is as a normative community institution, while power takes a role as an effective community organizing institution. The questions in this research are how do political ethics take a role in creating a modern democratic state?And what is the form of political ethics in the human political dimension? The research method used is a literature study approach. This study concludes that the human political dimension is a dimension of society as a whole. In terms of political ethics, the human political dimension can be studied in three cases. Those are humans as social beings, humans with their social dimensions, and the political dimensions of human life. Democracy is understood that state power is in the hands of the people. Thus, the people have the freedom to speak up their opinion in public. Power is needed to determine that humans obey the norms in the law. This research suggests that it is important to pay attention to the balance between the law and power to create a modern democratic state.